Combining object detection and brain computer interfacing: Towards a new way of subject-environment interaction - Robben, A.; Chumerin, N.; Manyakov, N. V.; Combaz, A.; van Vliet, M.; Van Hulle, M. M. (2011 IEEE International Workshop on Machine Learning for Signal Processing, 2011)
In this paper, we present an application that is a synergy of two research disciplines: visual object detection (and localization) and brain-computer interfacing. The goal is to construct an alternative way for a person to select real objects in the environment, without using speech, or any other form of muscular activity. Due to the latter, our application is potentially useful for patients that suffer from severe motor impairments since it would enable them to engage in a high-level interaction process with objects.